2022
DOI: 10.1002/anie.202203264
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Allylic Alcohol Formation by a Multifunctional Cytochrome P450 Monooxygenase with Rare Redox Partners

Abstract: Caryoynencin is a toxic and antifungal fatty acid derivative produced by a number of plant‐pathogenic and insect‐protective bacteria (Trinickia caryophylli and Burkholderia spp.). In addition to the reactive tetrayne unit, the presence of an allylic alcohol moiety is critical for antimicrobial activities. By a combination of mutational analyses, heterologous expression and in vitro reconstitution experiments we show that the cytochrome P450 monooxygenase CayG catalyzes the complex transformation of a saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Since the C18 protegencin and caryoynencin are the major products in the cultivation of P. protegens and T. caryophylli , respectively, one would expect octadecanoid fatty acids to be the primary substrates for PgnG and CayD. Nonetheless, we also noted polyyne tetradecanoid and hexadecanoid fatty acids in P. protegens Pf‐5, which suggested that either shorter chain lengths are accepted as substrates by the polyyne biosynthesis enzymes, or that the C18 products are shortened by β‐oxidation [8b] . The ACP loading experiments demonstrate that there is some flexibility with regard to chain length in the ligase‐ACP system, and further substrate control is likely during the downstream processes.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Since the C18 protegencin and caryoynencin are the major products in the cultivation of P. protegens and T. caryophylli , respectively, one would expect octadecanoid fatty acids to be the primary substrates for PgnG and CayD. Nonetheless, we also noted polyyne tetradecanoid and hexadecanoid fatty acids in P. protegens Pf‐5, which suggested that either shorter chain lengths are accepted as substrates by the polyyne biosynthesis enzymes, or that the C18 products are shortened by β‐oxidation [8b] . The ACP loading experiments demonstrate that there is some flexibility with regard to chain length in the ligase‐ACP system, and further substrate control is likely during the downstream processes.…”
Section: Resultsmentioning
confidence: 73%
“…Nonetheless, we also noted polyyne tetradecanoid and hexadecanoid fatty acids in P. protegens Pf‐5, which suggested that either shorter chain lengths are accepted as substrates by the polyyne biosynthesis enzymes, or that the C18 products are shortened by β‐oxidation. [8b] The ACP loading experiments demonstrate that there is some flexibility with regard to chain length in the ligase‐ACP system, and further substrate control is likely during the downstream processes. The predicted tertiary structures of CayD and PgnG obtained by AlphaFold2 [14] revealed that these proteins possess a typical ACP fold with three main α‐helixes that run parallel to each other (Figure S3).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Mutational analyses, heterologous expression and in vitro reconstitution experiments have identified CayG, a cytochrome P450 monooxygenase that catalyses allylic alcohol formation from a saturated carbon chain during the biosynthesis of the antifungal fatty acid, caryoynencin 22 . 17 Additional studies, including in vitro biotransformations with biosynthetic intermediates revealed the transformation follows a desaturation–hydroxylation sequence. The biosynthetic programming of highly methylated polyene α-pyrones has been investigated using the polyketide phytotoxin, alternapyrone 23 .…”
mentioning
confidence: 99%